Digital media in a contemporary conflict – example of Ukraine - Galus, Aleksandra; Nesteriak, Yuliia (Wydawnictwo Naukowe WNPiD UAM, 2019)
The ongoing conflict between Ukraine and Russia provides many examples of using media, including technologically new ones, to conduct information warfare. The article focuses on the issue of the importance of digital media in the context of war in eastern Ukraine and socio-political protests (2013/2014) that preceded the armed conflict. This article analyzes the methods of instrumental usage of digital media by Russia as the dominant entity in conducting aggressive information warfare against Ukraine as well as civic actions on the Ukrainian side aimed at counteracting Russian propaganda. The results show that, in the times of the mediatization of war, different entities tend to actively use both traditional media present in the digital space and social media. In addition, this work systematizes the conceptual apparatus related to the discussed issues. The article is based on the analysis of case studies (mainly Russian RT and Ukrainian, social initiative StopFake), content analysis, analysis and criticism of literature, and examination of source studies. The article complements the current debate on the conflict between Ukraine and Russia by highlighting the role of digital media in the context of information warfare and by showing that digital media, especially social media, can be a platform adopted not only by state actors, but also for citizens.

Trwający konflikt rosyjsko-ukraiński dostarcza wielu przykładów wykorzystywania mediów, także tych technologicznie nowych, do prowadzenia walki informacyjnej. Artykuł koncentruje się na problemie znaczenia mediów cyfrowych w warunkach wojny na wschodzie Ukrainy oraz w okresie protestów społeczno-politycznych z przełomu 2013/2014 roku, które poprzedziły konflikt zbrojny. W artykule dokonano analizy sposobów instrumentalnego wykorzystywania mediów cyfrowych przez Rosję jako podmiot dominujący w prowadzeniu agresywnej walki informacyjnej przeciwko Ukrainie oraz działań obywatelskich po stronie ukraińskiej, których celem było przeciwdziałanie rosyjskiej propagandzie. Wskazano, że w czasach mediatyzacji wojny, poszczególne podmioty aktywnie korzystają zarówno z tradycyjnych mediów, które są obecne w przestrzeni cyfrowej, jak i z mediów społecznościowych. Ponadto, w pracy dokonano usystematyzowania aparatury pojęciowej związanej z dyskutowaną problematyką. Artykuł oparty jest o analizę studiów przypadku (przede wszystkim działalności rosyjskiej telewizji RT i ukraińskiej, społecznej inicjatywy StopFake), analizę treści, analizę i krytykę piśmiennictwa oraz badanie opracowań źródłowych. Praca uzupełnia aktualną debatę na temat konfliktu zbrojnego pomiędzy Ukrainą i Rosją poprzez zwrócenie uwagi na rolę mediów cyfrowych w kontekście walki informacyjnej oraz ukazanie, że media cyfrowe, szczególnie media społecznościowe, mogą stanowić platformę działania nie tylko dla aktorów państwowych, lecz również obywateli.
Media cyfrowe we współczesnym konflikcie – przykład Ukrainy
Keywords: civil society; digital media; information warfare; Russia; social media; Ukraine; media cyfrowe; media społecznościowe; Rosja; społeczeństwo obywatelskie; Ukraina; walka informacyjna